LIP3D Project: LIving forever the Past through a 3Digital World - Pepe, Massimiliano; Menozzi, Oliva; Costantino, Domenica; Alfio, Vincenzo Saverio; Maravelaki, Emmanuel; Mailis, Athanassios; Abate, Dante (My University, 2025)
The Living Forever the Past through a 3Digital World (Lip3D) project is focused on advancing a range of interconnected activities at each archaeological site, which will establish a shared workspace that features 3D digitization of archaeological locations, virtual reality experiences of reconstructed environments, gamified site maps, and educational gaming. The LIP3D Project provides an important contribute in: i) advancement of 3D and XR Digitization Technologies, ii) accessibility and Distribution of Digitized Cultural Heritage, iii) creation and utilization of comprehensive 3D Cultural Heritage datasets, and iv) empowerment and Integration in Cultural Heritage Digital Transformation.
Keywords: LIving forever; Digitized Cultural Heritage